Laparoscopic Resection of Pancreatic Tail Solid Pseudopapillary Tumour in a Young Male - W. G. P. Kanchana; R. A. A. Shaminda; K. B. Galketiya; V. Pinto; D. Walisinghe; S. Wijetunge; R. Heendeniya (Case Reports in Gastrointestinal Medicine)
Background. Solid Pseudopapillary Tumours of the pancreas are a rare entity and more commonly seen in women than in men. These tumours have typically reached large sizes when clinically detected. Case Description. A 21-year-old male was found to have a left hypochondrial mass on physical examination following a trivial soft tissue injury. Contrast-enhanced computed topography (CT) of the abdomen showed a 10.3 × 7.6 × 10.3 cm size arising from the body and the tail of the pancreas. He underwent laparoscopic resection of distal pancreatic tumour en bloc with spleen. Large tumour was noted originating from the body and tail of the pancreas with dilated veins surrounding the tumour. Histology revealed a clear cell variant of solid pseudopapillary neoplasm with steatotic pattern. Resection margin was free of tumour. Discussion. Several studies have shown significant short term advantages using laparoscopic approach compared to open surgery, in terms of lower blood loss, resumption of oral intake, and hospital stay. This case and few other case reports published in world literature have shown that laparoscopic approach is safe and oncologically adequate.